Plasma selenium and its relation to cardiovascular risk parameters in obese women (Research, Society and Development, 2019)
The present study aims to evaluate the relationship between selenium plasma concentration and cardiovascular risk in obese women. This is a case-control study, involving 67 women, aged between 20 and 50 years, and divided into two groups: control group (eutrophic women, n = 42) and case group (obese women n = 25). Plasma selenium and lipid profile (total cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol and VLDL-cholesterol) were analyzed. Data were analyzed using the SPSS for Windows 22.0 statistical program. The project was approved by the Research Ethics Committee of the Federal University of Piauí, under opinion number 2.014.100. Regarding the results, lower concentrations of plasma selenium were observed for the obese group, with a statistically significant difference between the groups (p